High Neutralizing Antibody Levels Against Severe Acute Respiratory Syndrome Coronavirus 2 Omicron BA.1 and BA.2 After UB-612 Vaccine Booster . (20th June 2022) - Guirakhoo, Farshad; Wang, Shixia; Wang, Chang Yi; Kuo, Hui Kai; Peng, Wen Jiun; Liu, Hope; Wang, Lixia; Johnson, Marina; Hunt, Adam; Hu, Mei Mei; Monath, Thomas P; Rumyantsev, Alexander; et al.
Abstract: The highly transmissible severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) Omicron variant has caused high rates of breakthrough infections in those previously vaccinated with ancestral strain coronavirus disease 2019 (COVID-19) vaccines. Here, we demonstrate that a booster dose of UB-612 vaccine candidate delivered 7–9 months after primary vaccination increased neutralizing antibody levels by 131-, 61-, and 49-fold against ancestral SARS-CoV-2 and the Omicron BA.1 and BA.2 variants, respectively. Based on the receptor-binding domain protein binding antibody responses, the UB-612 third-dose booster may lead to an estimated approximately 95% efficacy against symptomatic COVID-19 caused by the ancestral strain. Our results support UB-612 as a potential potent booster against current and emerging SARS-CoV-2 variants. Abstract : A booster dose of UB-612, a next-generation subunit protein-peptide vaccine, induced high cross-reactive antibodies against SARS-CoV-2 variants and is predicted to confer approximately 95% efficacy against symptomatic COVID-19 caused by the ancestral SARS-CoV-2 strain.